2021
DOI: 10.1017/s0950268821002089
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of and responses to the two COVID-19 outbreak waves in Hebei Province of China, January 2020 to February 2021

Abstract: Hebei Province was affected by two coronavirus disease 2019 (COVID-19) outbreak waves during the period 22 January 2020 through 27 February 2020 (wave 1) and 2 January 2021 through 14 February 2021 (wave 2). To evaluate and compare the epidemiological characteristics, containment delay, cluster events and social activity, as well as non-pharmaceutical interventions of the two COVID-19 outbreak waves, we examined real-time update information on all COVID-19-confirmed cases from a publicly available database. Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several studies have compared the characteristics of hospitalized patients during different waves of COVID-19 [ 15 , 24 , 25 , 26 , 27 ]. However, these studies were early in the pandemic and reported the first two waves using different variables and parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared the characteristics of hospitalized patients during different waves of COVID-19 [ 15 , 24 , 25 , 26 , 27 ]. However, these studies were early in the pandemic and reported the first two waves using different variables and parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, about 98% of the infected hospitalized patients during the Omicron wave were nationals, compared to 77% during the first wave caused by the novel COVID-19 virus. Ethnicity has not been confirmed as a risk factor for negative outcomes in COVID-19 patients [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The potential factors behind the differences in the first wave are the dense living conditions of the non-nationals and their lack to prompt access to medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was a small contagion chain, it illustrated the advantages of this kind of analysis. Cheng covered information on contagion chains in an analysis of the two COVID-19 outbreak waves in Hebei Province, China [10]. Likewise, Hu et al analyzed a chain of transmission involving 52 linked patients with COVID-19 in three separate hospitals in Wuhan [11].…”
Section: Related Workmentioning
confidence: 99%
“…In late January 2021, there was a localized pandemic in Hebei Province, with more than 85% of infected patients coming from rural areas ( 8 ). Different from the early 2020 this time the pandemic broke out and spread widely in rural areas.…”
Section: Introductionmentioning
confidence: 99%